Cerebral infarction pattern in tuberculous meningitis - Tai, M.L.S. (Nature Publishing Group, 2016)
Tuberculous meningitis (TBM) causes significant morbidity and mortality. The primary objective was to re-examine the concept of "TB zone" and "ischaemic zone" in cerebral infarction in patients with tuberculous meningitis. The secondary objective was to evaluate cerebral infarction, vasculitis and vasospasm in tuberculous meningitis infections. Between 2009 and 2014, TBM patients were recruited. Neuroimaging was performed and findings of cerebral infarction, vasculitis and vasospasm were recorded. Infarcts were classified based on arterial supply and Hsieh's classification. Fifty-one TBM patients were recruited of whom 34 patients (67%) had cerebral infarction. Based on Hsieh's classification, 20 patients (59%) had infarcts in both "TB zone" and "ischaemic zones". 12 patients (35%) had infarcts in "ischaemic zone" and two (6%) patients had infarcts in "TB zone". In terms of vascular supply, almost all patients (35/36) had infarcts involving perforators and cortical branches. 25 patients (73%) and 14 patients (41%) had infarcts supplied by lateral lenticulostriate and medial lenticulostriate arteries respectively. 15 patients (37%) had vasculitis. Vasospasm was present in six patients (15%). 29 patients (85%) with cerebral infarction also had leptomeningeal enhancement (p = 0.002). In summary, infarcts involved mainly perforators and cortical branches, rather than "TB zone" versus "ischaemic zone".